AN ANALYZING OF USING SIMPLE PRESENT TENSE AND SIMPLE PAST TENSE IN ACTUALIZING WRITING SKILL OF MTS RAUDLATUTTHOLIBIN (RTH) NW PAOKMOTONG - M. Mizanul Haq; Rosfin Hidayati; Siti Wahyu Puji Anggraini (Berugak Baca, 2024)
This study intended to Analyze the use of Simple present tense and Simple Past Tense in Actualizing Writing Skill of MTs Raudlatuttholibin (RTH) NW Paokmotong Students. Which has one classes, it is consist of 40 students but the writer just takes 30 of the students as the sample of this research. To get the data needed, the writer used two research instruments in the form of simple present tense and simple past tense test. The students were given 10 question and five question from ten question asked them to describe some picture and five question again students just translate the sentence from Indonesian to English language. Having analyzed the whole data obtained it is found out that the student’s error and student’s goal. In the test of simple present tense and simple past tense is considered fairly good with the mean score is 60. Finally, the writer knows the problem of the students and for the next researcher’s undertake a large investigation in to the same research is.